Admission Hyperglycemia and Acute Myocardial Infarction: Outcomes and Potential Therapies for Diabetics and Nondiabetics. (9th July 2012) - Chakrabarti, Anjan K.; Singh, Priyamvada; Gopalakrishnan, Lakshmi; Kumar, Varun; Elizabeth Doherty, Meagan; Abueg, Cassandra; Wang, Weici; Gibson, C. Michael
Abstract : Hyperglycemia, in both diabetic and nondiabetic patients, has a significant negative impact on the morbidity and mortality of patients presenting with an acute myocardial infarction (AMI). Contemporary evidence indicates that persistent hyperglycemia after initial hospital admission continues to exert negative effects on AMI patients. There have been a number of studies demonstrating the benefit of tight glucose control in patients presenting with AMI, but a lack of convincing clinical data has led to loose guidelines and poor implementation of glucose targets for this group of patients. The CREATE-ECLA study, which hypothesized that a fixed high dose of glucose, insulin, and potassium (GIK) would change myocardial substrate utilization from free fatty acids to glucose and therefore protect ischemic myocardium, failed to demonstrate improved clinical outcomes in AMI patients. Studies that specifically investigated intensive insulin therapy, including DIGAMI-2 and HI-5, also failed to improve clinical outcomes such as mortality. There are a number of reasons that these trials may have fallen short, including the inability to reach glucose targets and inadequate power. There is now a need for a large placebo-controlled randomized trial with an adequate sample size and adherence to glucose targets in order to establish the benefit of treating hyperglycemia in patients presenting with AMI.